2016
DOI: 10.3889/oamjms.2016.037
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Cardiovascular Risk Factors in Obese Adolescent

Abstract: BACKGROUND:Childhood and adolescent obesity is associated with insulin resistance, abnormal glucose metabolism, hypertension, dyslipidemia, inflammation, liver disease, and compromised vascular function. The purpose of this study was to determine the prevalence of cardiovascular risk factor abnormalities and metabolic syndrome in a sample of obese adolescent as prevalence data might be helpful in improving engagement with obesity treatment in future. The high blood lipid levels and obesity are the main risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
1
6
0
3
Order By: Relevance
“…That study also reported an association between hypertension in mothers and prehypertension in children (OR 1.96; CI 95% 1.15-3.36) (16). Overall, these studies support our results because they indicate that hypertension and obesity in children are associated with hypertension and obesity in parents (15,17). According to the World Health Organization (WHO), excess body mass is responsible for 20% to 30% of hypertension cases (18).…”
Section: Resultssupporting
confidence: 85%
“…That study also reported an association between hypertension in mothers and prehypertension in children (OR 1.96; CI 95% 1.15-3.36) (16). Overall, these studies support our results because they indicate that hypertension and obesity in children are associated with hypertension and obesity in parents (15,17). According to the World Health Organization (WHO), excess body mass is responsible for 20% to 30% of hypertension cases (18).…”
Section: Resultssupporting
confidence: 85%
“…Seventy six articles were included in the nal analysis in this meta-analysis. Twenty ve studies were excluded due to the following exclusion criteria: different study population [109][110][111][112][113], no full test [114][115][116][117], unclear diagnostic criteria [118][119][120][121][122][123][124][125], letter to editor [126], written in non English language [127,128], and different study design [129][130][131][132][133] (Fig. 1).…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%
“…Overweight, physical inactivity, inadequate diet and improper lifestyle habits in general, in addition to secondary causes such as diabetes mellitus, hypothyroidism, among others, are involved in the onset of dyslipidemia [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%